A Comparison Study of Chemical Compositions and Sources of PM1.0 and PM2.5 in Hanoi - Pham Duy Hien; Vuong Thu Bac; Nguyen Thi Hong Thinh; Ha Lan Anh; Duong Duc Thang; Nguyen The Nghia (Aerosol and Air Quality Research)
Abstract We simultaneously collected 85 pairs of 24-h PM1.0 and PM2.5 samples from a new urban area in Hanoi, Vietnam, and analyzed their chemical compositions with particle-induced X-ray emission (PIXE) and ion chromatography (IC) to obtain input data for source apportionment via positive matrix factorization (PMF). Sulfate, ammonium, and black carbon (BC) composed the majority of the mass in both size fractions, and the PMF models clearly differentiated the contribution of long-range transport (LRT) aerosols, which accounted for more than two-thirds of the measured PM-bound sulfate and ammonium concentrations, from those of the six in situ sources, viz., resuspended road dust, primary vehicular emissions, coal fly ash, biomass burning emissions, construction dust, and sea salt. Whereas LRT aerosols, coal fly ash, and primary particulate vehicular emissions mainly occurred in the PM1.0, resuspended road dust and biomass-burning fly ash tended to appear in the PM1.0–2.5; hence, we can characterize the anthropogenic emissions in this area by examining the profile of the PM1.0 rather than the PM2.5. Additionally, air masses with inland trajectories originating in northern China and countries northwest and southwest of Vietnam contained more ammonium, sulfate, and BC than those that passed over the East Sea. Finally, the LRT aerosols exhibited high acidity in the PM1.0 but neutrality in the PM2.5.